UMPSA joins MAGNET 2024 Programme A Platform for International Student Unity - Muhammad Zufli, Zuhari (UMPSA, 2024)
PUTRAJAYA, 27 November 2024 – The Meet and Greet with International Students in Malaysia (MAGNET) 2024 programme was successfully held at Taman Botani Putrajaya, bringing together 658 international students from various countries.